Teori Motivasi, Kinerja dan Prestasi Kerja dalam Al-Quran Serta Pleksibilitas Penerapannya pada Manajemen Perbankan Islam - Maguni, Wahyudin; Maupa, Haris (Li Falah: Journal of Islamic Economics and Business, 2018)
In principle what has been discussed by experts on the theory of Work Motivation,Performance, and Achievement, from the results of the research Journal review obtained definitions as well as indicators on each theory which is a variable that is motivation, performance and work performance, essentially there is an explanation and legal source in the Koran. This is a strengthening and meaning for these variables. This is evidence that the Koran as a divine word is the greatest source of knowledge that we can learn and understand and practice in everyday life. Developing theoretical theories such as motivation, performance and work performance, can be applied and practiced in a general organization, business environment, and included in Islamic Banking. Motivation is the process of influencing or encouraging from outside to a person or work group in order to want to carry out something that has been determined (Samsudin, 2005: 281). Furthermore Performance is the real behavior displayed by each person as workperformance produced by employees in accordance with their role in the organization.Employee performance is a very important thing in the organization's efforts to achieve its goals.And on the next point is work achievement which is one measure of the work of a person in a company organization and becomes one of the considerations in the implementation of promotion. The achievement of one's work can be seen based on the qualifications possessed, namely skills, skills, experience and environment work (adaptability).